Paroxysmal nocturnal haemoglobinuria with dysphagia. A case report - Riadi Wirawan, Riadi Wirawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
We reported a case of a 32 year old male with diagnosis thalassaemia and dysphagia who had been hospitalized four times at two different private hospitals. The chief complaints were weakness, brownish red discoloration of urine at night until morning and dysphagia. Physical examination revealed hepatosplenomegaly. The laboratory findings were normocytic normochromic anaemia, pancytopenia, reticulocytosis, hyperactive erythropoiesis, decreased NAP score, positive Hams test and sugar water test. These findings were in accordance with intravascular haemolytic anaemia caused by PNH. Dysphagia in this case is one of clinical manifestation of PNH. We also found disorder of liver function test such as increased transaminase activity and gGT which may be caused by cholestasis, which should be confirmed by USG.Key words : intravascular haemolytic anaemia - dysphagia - haemoglobinuria - cholestatis - pancytolemia